2006
DOI: 10.1177/1087057106289231
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Caspase-3 Inhibitors: Effect of a Reducing Agent on Identified Hit Chemotypes

Abstract: When studying cysteinyl proteases in general and caspases in particular, it is generally accepted that a reaction buffer must contain a reducing agent to prevent essential cysteinyl groups from spontaneous oxidation. Dithiothreitol (DTT) and beta-mercaptoethanol (beta-MCE) are 2 of the most broadly used reducing agents. While screening a library of small molecules against caspase-3, the authors have found that the nature of the reducing agent used, DTT or beta-MCE, dramatically affects screening results and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Previously Okun et al (32) found that in the presence of ␤-mercaptoethanol the inhibitory activity of 1,3-dioxo-2,3-dichloro-1H-pyrrolo [3,4-c]quinolines, which were identified as selective and reversible inhibitors of caspase-3 from screening in a DTT-containing buffer could not be measured. It was proposed that DTT and ␤-mercaptoethanol differentially affect the enzymatic parameters and the thermoinactivation of caspase-3 and thus define its sensitivity to different chemo types of small molecule inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously Okun et al (32) found that in the presence of ␤-mercaptoethanol the inhibitory activity of 1,3-dioxo-2,3-dichloro-1H-pyrrolo [3,4-c]quinolines, which were identified as selective and reversible inhibitors of caspase-3 from screening in a DTT-containing buffer could not be measured. It was proposed that DTT and ␤-mercaptoethanol differentially affect the enzymatic parameters and the thermoinactivation of caspase-3 and thus define its sensitivity to different chemo types of small molecule inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, these agents had only weak effects on the inactivation by compound III (even in 100 M) ( Table 2). Lipoic acid and some other dithiol-containing agents (such as 1,2-butanedithiol, 1,4-butanedithiol, 1,2-benzenedithiol, and 4,4Ј-thiobisbenzenthiol) have been reported to be able to facilitate 1,3-dioxo-2,3-dihydro-1H-pyrrolo [3,4-c]quinolines to produce the same potent inhibition of caspase-3 as DTT (32). However, our results show that dihydrolipoic acid (reduced lipoic acid) but not lipoic acid has a great effect on the sensitivity of caspase-3 to isoquinoline-1,3,4-trione derivatives (Table 2).…”
Section: Time-dependent Irreversible Inactivation Of Caspase-3 By Isomentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of both our findings and previously reported effects on the ability of reductants to alter Caspase-3 catalytic activity and inhibition [17], the effects of varying reductants on the enzymatic activity of USP7 were examined. Activity measurements were therefore taken immediately after incubation of the enzyme in buffer containing no additional reductant (other than remaining TCEP from the storage buffer), 1 mM DTT, 1 mM Cysteine, 1 mM glutathione, or 1 mM TCEP.…”
Section: Discussionmentioning
confidence: 98%
“…This is in contrast to some other cysteine proteases, such as caspase-3, where the presence of different reductants not only affects the catalytic activity, and potentially structural modification of the enzyme, but also the enzyme's sensitivity to small molecules of different chemotypes [17].…”
Section: Discussionmentioning
confidence: 98%